RETRACTED: Opa1 Reduces Hypoxia-Induced Cardiomyocyte Death by Improving Mitochondrial Quality Control - Xin, Ting; Lv, Wei; Liu, Dongmei; Jing, Yongle; Hu, Fang (Frontiers in Cell and Developmental Biology, 2020)
Mitochondrial dysfunction contributes to cardiovascular disorders, especially post-infarction cardiac injury, through incompletely characterized mechanisms. Among the latter, increasing evidence points to alterations in mitochondrial quality control, a range of adaptive responses regulating mitochondrial morphology and function. Optic atrophy 1 (Opa1) is a mitochondrial inner membrane GTPase known to promote mitochondrial fusion. In this study, hypoxia-mediated cardiomyocyte damage was induced to mimic post-infarction cardiac injury in vitro. Loss- and gain-of-function assays were then performed to evaluate the impact of Opa1 expression on mitochondrial quality control and cardiomyocyte survival and function. Hypoxic stress reduced cardiomyocyte viability, impaired contractile/relaxation functions, and augmented the synthesis of pro-inflammatory mediators. These effects were exacerbated by Opa1 knockdown, and significantly attenuated by Opa1 overexpression. Mitochondrial quality control was disturbed by hypoxia, as reflected by multiple mitochondrial deficits; i.e., increased fission, defective fusion, impaired mitophagy, decreased biogenesis, increased oxidative stress, and blunted respiration. By contrast, overexpression of Opa1 normalized mitochondrial quality control and sustained cardiomyocyte function. We also found that ERK, AMPK, and YAP signaling can regulate Opa1 expression. These results identify Opa1 as a novel regulator of mitochondrial quality control and highlight a key role for Opa1 in protecting cardiomyocytes against post-infarction cardiac injury.